THE LINGUISTIC AESTHETICS OF TRADITIONAL BUGIS BONE POETRY: A STYLISTIC ANALYSIS AND CULTURAL VALUE - Harun, Muhammad; Halim, Nurfitriyah (Lembaga Jurnal FKIP Universitas Bosowa, 2025)
This study examines how traditional Bugis verbal art, particularly materials circulating in Bone, generates aesthetic force through patterned language while simultaneously articulating ethical meaning. Focusing on two forms widely recognised in Bugis cultural practice pappaseng (advice or wisdom sayings) and elong (poetic song or verse), the study approaches these texts as objects of literary analysis within a stylistic framework. Using qualitative document analysis and close stylistic reading, six short excerpts are analysed, drawn from publicly available sources that include a Bone court dialogue, pappaseng formulas, a widely cited reso proverb, and two elong stanzas. Across the excerpts, recurrent stylistic devices include parallel question answer framing, triadic listing, rhythmic clause chaining, symbolic ‘fence’ (sappo) metaphors, and hyperbolic imagery. These patterned forms condense moral reasoning into memorable verbal structures, enabling values such as lempu’ (integrity), siri’ (honour/shame), and reso (persevering effort) to be articulated, recalled, and circulated in everyday interaction. As the corpus is documentary rather than field recorded, the interpretations advanced here remain text centred and open to further refinement through engagement with Bugis speakers and cultural practitioners.